A Study on Sociodemographic Profile and Pattern of Injuries in Road Traffic Accidents amongst Pillion Riders in Chennai (Indian Journal of Forensic Medicine & Toxicology, 2020)
One of the widespread preventable cause of unnatural death is Road Traffic Accidents. ARetrospective cross sectional study of the sociodemographic profile of pillion riders beingvictims of Road traffic accidents, the circumstances leading to road traffic accidents, the patternand severity of injuries of occurring in Chennai was conducted in Saveetha Medical Collegeand Hospital, Thandalam, Chennai, Tamilnadu. A total of 2438 cases of Road traffic accidentswere recorded for a year (JAN2018-DEC2018).Out of which 62 cases (2.5%) of Road trafficaccidents deals with the injuries of pillion riders. Among the pillion riders, Male outnumberedthe Females(1.11 : 1). The most vulnerable age group was 21-30 years(50%). Most frequentof all is Head and Neck injuries and Injuries on the Upper limb. The information obtained canserve as a guide for better management of victims of Road traffic accidents and to establishRoad safety measures.